The Influence of Parental Conflict on Adolescent Depression - Chen, Jiarui (Transactions on Social Science, Education and Humanities Research, 2024)
Harmonious family relationships are significant for adolescent development, and the purpose of this study is to investigate the effects of parental conflict in the family on adolescent depression. Through the study of the effects of parental conflict on depression in adolescents, this study recognizes the link between parental conflict and depression in adolescents, understand the development of their depression, and then provide new strategies for families, communities, schools, and society to improve the mental health on adolescents, to prevent adolescents from depression and provide them with practical methods of guidance. The first part of the study concludes parental conflict has a positive predictive effect on adolescent depression. Then the second part concludes that effective parental conflict resolution has a mitigating effect on adolescent depression. The third part of this paper suggests multifaceted method to rationally play the roles of family and school to reduce parental conflict and ease the tense family atmosphere, which is conducive to the healthy development of adolescents’ physical and mental health. The findings of this study contribute to the study of factors influencing adolescent mental health and it is useful for establishing family education interventions based on adolescent mental health.